Effects of live yeast on milk yield, feed efficiency, methane emissions and fertility of high-yielding dairy cows - P.C. Garnsworthy; N. Saunders; J.R. Goodman; I.H. Algherair; J.D. Ambrose (Animal)
Live yeast (Saccharomyces cerevisiae) products have the potential to increase milk yield of dairy cows in early lactation by improving rumen fermentation. Greater milk yields, however, are sometimes associated with poorer reproductive performance. This study aimed to assess the effect of a live yeast supplement on milk yield, methane emissions and reproduction indicators in high−yielding dairy cows. Fifty Holstein cows were paired according to month of calving, parity and predicted milk yield, and allocated at random to either a Control diet or a diet containing live Yeast (Actisaf® Sc 47, 1 × 1010 cfu/g, Phileo by Lesaffre) supplying 1 × 1011 cfu/cow per day (10 g). Diets were fed to cows from 7 to 128 days in milk. Live yeast resulted in higher yields of milk (50.1 vs 47.5 kg/day), energy-corrected milk (ECM; 50.5 vs 47.7 kg/day), fat−corrected milk (49.2 vs 46.3 kg/day) and milk fat (1 945 vs 1 823 g/day), compared with Control. There was no effect of treatment on DM intake (DMI), so cows fed on Yeast had greater feed efficiency (2.11 vs 1.98 kg ECM/kg DMI). Enhanced milk yield and feed efficiency were attributed to higher digestibility coefficients for DM (0.80 vs 0.77), NDF (0.66 vs 0.62) and gross energy (0.81 vs 0.78) in cows fed on Yeast compared with Control. Rumen pH, redox potential and volatile fatty acid concentrations, methane emissions, plasma metabolites and immunity indicators, and health events were not affected by treatment. There was no effect of treatment on days from calving to first milk progesterone rise above 3 ng/ml, days to first insemination, days to conception, conception rate, number of inseminations or incidence of atypical ovarian cycles. It was concluded that live yeast enhanced digestibility, milk yield and feed efficiency in high-yielding dairy cows, and that despite increased milk yield, methane emissions, reproduction and health indicators were maintained at the same levels as control cows.